The Environmental Status of the Port of HaminaKotka - Brunila, Olli-Pekka (Publications of the Centre for Maritime Studies, University of Turku A 69, 2014)
This study is a part of the Ecologically Friendly Port Ust-Luga (EFP) project. The purpose of this study is to examine the environmental status of the Finnish ports and, more specifically, the Port of HaminaKotka. An analysis of the environmental status is performed mainly as a literature review, because the Finnish ports must comply with Finnish and EU legislation and with the binding international regulations and conventions created by different organizations. The International Maritime Organisation (IMO) has done groundbreaking work in the field of maritime safety and maritime environmental protection. The MARPOL convention has a great impact on decreasing pollution from international shipping and it applies to 99% of the world’s merchant tonnage. Pollution prevention covers: Oil pollution, Chemical pollution, Air pollution and GHG Emissions, Dumping of Wasted and Other Matters, Garbage, Sewage, Port Reception Facilities, Special Areas under MARPOL and Particularly Sensitive Sea Areas. There is also Pollution Prevention for other treaties like anti-fouling systems used on ships, the transfer of alien species by ships’ ballast water and the environmentally sound recycling of ships. There are more than twenty different EU and international regulations that influence ports and port operations in Finland. In addition, there is also national legislation that has an effect on Finnish ports. For the most part, the legislation for ports is common in the EU area, but the biggest and most important difference between the legislation in Finland and other EU countries is due to the Act on Environmental Impact Assessment Procedure. The Act states that the environmental impact assessment procedure shall be applied to projects that may have significant adverse environmental impacts, due to the special features of Finland`s nature and environment. In this Act, the term environmental impact refers to the direct and indirect effects inside and outside Finnish territory of a project or operations on human health, living conditions and amenity; soil, water, air, climate, organisms, interaction between them and biodiversity; community structure, buildings, landscape, townscape and cultural heritage; utilization of natural resources. In Finland, the Environmental Permit requires that ports collect all necessary information concerning environmental effects and make required reports to the Finnish authorities, stakeholders and the public. Commonly, environmental reporting is public and environmental achievements are emphasized in reporting and in media. At the moment, the problem in environmental reporting is that it’s difficult to compare data from different ports. There is enough data concerning the environmental effects and performance, but the manner of reporting and the quality of the data varies between ports. There are differences in the units and codes used, in some cases the information is not sufficient and it can even be rather unreliable. There are also differences regarding the subjects that are emphasized in reporting.

Tämä tutkimus on tehty osana Ecologically Friendly Port Ust - Luga (EFP) -hanketta. Tutkimuksen tarkoituksena on tutkia ja selvittää Suomen satamien sekä erityisesti HaminaKotka-sataman ympäristövalveutuneisuuden tilaa. Tutkimus on toteutettu lähinnä lainopillisena tutkimuksena, koska Suomen satamat noudattavat Suomen ja EU:n välistä lainsäädäntöä ja joissakin tapauksissa kansainvälisiä säädöksiä. Kansainvälinen Merenkulkujärjestö (IMO) on tehnyt uraauurtavaa työtä merenkulun turvallisuuden ja meriympäristön suojelussa. MARPOL-yleissopimuksella on ollut suuri vaikutus kansainvälisen laivaliikenteen aiheuttaman saastumisen vähentämisessä ja 99 % maailman laivastosta noudattaa sopimusta. Saastumisen ehkäisy kattaa öljypäästöt, kemikaalipäästöt, ilmansaasteet ja kasvihuonekaasupäästöt, jätteiden mereen laskemisen, jätteet, jätevesi, satamien jätteiden vastaanoton, MARPOL-yleissopimuksen määrittelemät erityisalueet ja erityisen herkät merialueet. Merien pilaantumista ehkäistään myös muilla sopimuksilla koskien mm. laivojen eliönestomaaleja, alusten painolastivesien mukana kulkeutuvia tulokaslajeja sekä alusten ympäristöystävällisempää kierrätystä. On olemassa yli kaksikymmentä eri EU- ja kansainvälistä säännöstä, jotka vaikuttavat Suomen satamiin ja satamien toimintaan. Lisäksi suomalaisten satamien tulee noudattaa myös kansallista lainsäädäntöä. Enimmäkseen lainsäädäntö on yhtäläinen EU:n alueen satamissa, mutta eroavaisuuksiakin löytyy. Näistä suurin ja tärkein perustuu lakiin ympäristövaikutusten arviointimenettelystä (YVA). Menettelyä sovelletaan hankkeisiin, joilla voi olla merkittäviä haitallisia ympäristövaikutuksia Suomen luontoon ja ympäristöön. Ympäristövaikutuksilla tarkoitetaan sellaisia suoria ja välillisiä vaikutuksia Suomen rajojen sisällä ja ulkopuolella, jotka voivat kohdistua ihmisten terveyteen, elinoloihin ja virkistyskäyttöön, maaperään, veteen, ilmaan, ilmastoon, organismeihin, luonnon monimuotoisuuteen, yhdyskuntarakenteeseen, rakennuksiin, maisemaan, kaupunkikuvaan ja kulttuuriperintöön sekä luonnonvarojen hyödyntämiseen. Suomessa ympäristölupa edellyttää, että satamat keräävät ympäristötietoja ja raportoivat niistä luvan myöntäjille, virkamiehille, eri sidosryhmille ja kansalaisille. Yleisesti ympäristöraportointi on avointa ja ympäristötekoja painotetaan raportoinnissa ja mediassa. Tällä hetkellä suurin ongelma ympäristöä koskevassa raportoinnissa on tiedon vertailtavuus. Ympäristötietoa kerätään jo riittävästi, mutta raportointikäytännöt vaihtelevat satamien välillä. Eroja voi olla yksiköissä, jätejakeiden numeroinnissa ja joissakin tapauksissa tietoja ei ole riittävästi tai ne voivat olla jopa epäluotettavia. Eroja esiintyy myös siinä, mitä asioita raportoinnissa korostetaan.